Familial chondrocalcinosis in the Chiloe Islands, Chile. Issue 3 (June 1975) - Reginato, A J; Hollander, J L; Martinez, V; Valenzuela, F; Schiapachasse, V; Covarrubias, E; Jacobelli, S; Arinoviche, R; Silcox, D; Ruiz, F
Abstract : Studies about chondrocalcinosis in the Chiloe Islands (Chile) showed the high frequency of the disease there and how most of it is aggregated in a few highly involved families. Pedigrees and the high degree of consanguinity among parents of index cases pointed to a recessive inheritance. The presence of common Caucasian anthropological features of genetic value in the patients and the lack of Indian mixture in three of the involved families, documented back to 1600, suggest a Caucasian origin of the mutation. Biochemical studies of the patients' synovial fluid showed a significant rise in pyrophosphate concentration. Calcium, phosphorus, and alkaline phosphatase concentrations were not different from a control group.